KITA BERSAMA - Septria Niko Amerta; Yensharti Yensharti; Ardipal Ardipal (SENDRATASIK UNP, 2014)
Abstract   Theme of this creation tell about the real life. The story about journey to build a band with some friend. It’s composed to be 3 part, first part telling about sadness, second part telling about struggle, the last part telling about sadness but spirit to survive. This music composed by rythim, melody, dynamics, and harmony, then this creation bound with artistic.   Keywords :  Art Creation, Music Composed, Telling, Life Story.